The efficacy of Tc99m dimercaptosuccinic acid (Tc-DMSA) scintigraphy and ultrasonography in detecting renal scars in children with primary vesicoureteral reflux (VUR) - ALPAY, HARİKA; TARCAN, TUFAN (SPRINGER, 2006)
Introduction: Pyelonephritis-induced renal scarring in children is a major predisposing factor for proteinuria, hypertension, and ultimate renal failure. The aim of this study was to investigate and compare the efficacy of Tc99m dimercaptosuccinic acid (Tc-DMSA) renal scintigraphy and renal ultrasonography (USG) in detecting renal scars in children with primary vesicoureteral reflux (VUR). Materials and methods: Tc-DMSA scan and USG studies were done in 62 children who were admitted to our clinic between 1997 and 2003 because of documented urinary tract infection (UTI) and diagnosed with primary VUR. Renal scarring detection rates of Tc-DMSA scan and USG were compared according to reflux grades. Results: In the whole group, renal scars were detected by Tc-DMSA scan and USG in 55% and 38% of refluxing units, respectively. Detection rates of Tc-DMSA and USG according to reflux grades were as follows: 47% and 29% in low-grade VUR (grades 1 and 2), 46% and 25% in mid-grade VUR (grade 3), 76% and 65% in high-grade VUR (grades 4 and 5), respectively. Conclusion: USG was found to be an inappropriate study in the detection of renal parenchymal scars, irrespective of the reflux grade. In this study, Tc-DMSA scan detected scars in 35% of kidneys reported to be normal on USG.
Keywords: DMSA scan; renal scar; ultrasonography; vesicoureteral reflux; URINARY-TRACT-INFECTIONS; POWER DOPPLER SONOGRAPHY; CORTICAL SCINTIGRAPHY; ACUTE PYELONEPHRITIS